Large Prostatic Calculus in an Alkaptonuria patient - Caught unaware - Sivasankaran Nachimuthu; Kallappan Senthil; Manickam Ramalingam (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Alkaptonuria, a metabolic disorder with urological manifestation goes unnoticed till we are aware of it. Here we present an alkaptonuric patient with difficult catheterisation was diagnosed with a large prostatic calculus and his management.